Relationship of Handedness with Second to Fourth Digit (2D: 4D) Ratio and its Role in Sexual Dimorphism in Tibeto-Nepalese and Indo-Nepalese Adult Population of the Dharan Municipality, Sunsari District of Eastern Nepal: An Anthropometric Study - Shah, Sandip; Koirala, Sarun; Khanal, Laxman (Journal of Morphological Sciences, 2019)
Introduction The importance of handedness lies in its relationship with the lateralization of the brain function, especially of language. The aim of the present study was to provide an authentic database on right and left second to fourth digit (2D:4D) ratios in 2 different ethnic groups of a particular age and gender, and to study its correlation with handedness and sexual dimorphism.Materials and Methods The present study was conducted among 400 Tibeto-Nepalese (TN) subjects (200 of each gender) and 400 Indo-Nepalese (IN) subjects (200 of each gender) aged ≥ 18 years old. The values for the 2D:4D ratio were calculated for both hands. Hand preference was established according to the Edinburgh Handedness Inventory, and five hand preference determination groups were constituted after the calculation of the laterality score. The results were tabulated and subjected to statistical analysis. A p-value < 0.05 was considered as statistically significant.Results The mean value of right sided 2D:4D ratio of TN female was higher as compared to IN female; and for left sided 2D:4D ratio, the value was lower in TN female as compared to IN female. When the values of the 2D:4D ratios were assessed by gender, the values were found to be statistically significant (p < 0.001), whereas when they were assessed by ethnicity, only the right hand 2D:4D ratio was found to be statistically significant (p < 0.001).Conclusion When the relationships between the laterality score and the 2D:4D ratios were examined, the values were found to be statistically significant in both ethnic groups only on the left side. The 2D:4D ratio shows significant ethnic and population differences in the present study.
Keywords: handedness; lateralization; tibeto-nepalese; indo-nepalese